2018
DOI: 10.1111/acfi.12373
|View full text |Cite
|
Sign up to set email alerts
|

Predicting FTSE 100 returns and volatility using sentiment analysis

Abstract: We investigate the statistical and economic effect of positive and negative sentiment on daily excess returns and volatility in the FTSE 100 index, using business news articles published by the Guardian Media Group between 01/01/2000 and 01/06/2016. The analysis indicates that while business news sentiment derived from articles aimed at retail traders doesn't influence excess returns in the FTSE 100 index, it does affect volatility, with negative sentiment increasing volatility and positive sentiment reducing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 52 publications
1
26
0
Order By: Relevance
“…Moreover, the presence of investor attention helps improve return efficiency. An increase in attention 5 Two other popular behavioral factors influencing stock market activities include investor mood (Harding and He 2016) and investor sentiment (Piccoli et al 2018 andJohnman et al 2018).…”
Section: Relevant Literaturementioning
confidence: 99%
“…Moreover, the presence of investor attention helps improve return efficiency. An increase in attention 5 Two other popular behavioral factors influencing stock market activities include investor mood (Harding and He 2016) and investor sentiment (Piccoli et al 2018 andJohnman et al 2018).…”
Section: Relevant Literaturementioning
confidence: 99%
“…Effects of temperature on stock market performance Negative sentiment's effect on financial returns and volatility is usually found to be stronger than positive sentiment (Johnman, Vanstone, & Gepp, 2018). Chang et al (2006) have confirmed an existence of a significant relationship between temperature, cloud cover and stock returns.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…In earlier periods, individual investors tended to be viewed as noise traders in the sense of Kyle (1985) and Black (1986), pushing asset prices away from fundamental values and destabilising markets because they were subject to fads and behavioural bias and returned poor performance. 1 At the same time, Johnman et al (2018) find that individual investors can influence market volatility. In recent years, however, financial economists have come to understand the importance of individual investors to financial markets.…”
Section: Introductionmentioning
confidence: 99%